Visualization of tests for future active safety and self-driving cars - Pernerstorfer, Matthias; Thangaswamy, Rajesh (My University, 2016)
This thesis investigates how sensor data of autonomous vehicles can be visualized in order to make it easier for humans to understand and analyze the data. To achieve this goal, the requirements of a software architecture of a tool that generates such visuals are elicited together with the details that should be included in said visuals. The result of this elicitation phase is used to develop such a software architecture. Furthermore, different technologies are compared that can be used to implement a tool that uses the created architecture. For this, a feasibility study is done that investigates which technologies are suitable to fulfill the elicited requirements. This thesis also finds a way how the deviations in the data of different sensors measuring the same object can be visualized. The objects recognized by the different sensors should be at the same place, however, it is possible that the measurements differ. Those differences have to be visualized. The results of this thesis for the software engineering body of knowledge include a software architecture that is able to fulfill the elicited requirements, as well as the results of the feasibility study, that shows what is and is not possible when using different technologies to implement a similar tool. Furthermore, a reference solution based on some of the technologies is implemented and described in this thesis.
Keywords: Data- och informationsvetenskap; Computer and Information Science